Tradition of Using Susungan to Carry Corpses to Cemetery on The Custom of Death in Nagari Bukit Tantang, Bukit Sundi District Solok Regency - Amalia Lubis, Riski; Endrizal (Kirana Publisher (KNPub), 2025)
This research is entitled